Authors and their ideas: a study os the intellectual elite and the political discourse of the Estado Novo regime in Brazil (1937-1945) - Codato, Adriano (2003)
This paper is an analysis of Estado Novo's political ideology, through the study of the magazine Cultura Política: revista mensal de estudos brasileiros, government¿s official periodic. After having read selected articles, concerning the political organization instituted in Brazil by the Golpe de 37, it was possible to examine intellectuals¿ rationalizations for the building of a strong and centralized national state in Brazil. At the end we could verify the role played by the magazine on the authoritarian regime, realize the burocracy¿s importance as producers of this ideological discourse, and distinguish some of its characteristics.